IDENTIFICATION OF BIOACTIVE COMPOUNDS BY GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS OF SYZYGIUM JAMBOS (L.) COLLECTED FROM WESTERN GHATS REGION COIMBATORE, TAMIL NADU - j, Devakumar; v, Keerthana; ss, Sudha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to investigate the presence of bioactive compounds in the methanolic leaf extract of Syzygium jambos. Methods: Collected leaves were shade dried and made into fine powder, extracted with methanol, and the methanolic extract was prepared and analyzed for the presence of bioactive compounds by gas chromatography-mass spectrometry (GC-MS). The mass spectrum of the chromatography was matched with NIST and WILEY Libraries. Results: The GC-MS analysis revealed the presence of 45 active compounds in the extract. From the GC-MS investigation, 1-Deoxy-d-mannitol3-methyl-2-methylsulfanyl-5-nitro-6-pyridin-4-ylpyrimidin-4-one, 3-Pentadecylphenol, 2-biphenylene carboxylic acid, Quinoline-3-carboxylic acid, and Stigmast-5-en-3-ol are important phytoconstituents which have antipyretic and antiparasitic activities. Conclusion: The present investigation revealed preliminary information on phytocompounds presented in S. jambos leaf extract which is very useful for the human community. Keywords: Syzygium jambos, Gas chromatography-mass spectrometry analysis, 1-Deoxy-d-mannitol, Phytoconstituents, Methanolic leaf extract